ANGKA KEJADIAN DIARE BALITA TAHUN 2014 DI PUSKESMAS BANGUNTAPAN I BANTUL YOGYAKARTA - Budi Rahayu, Afrianti; Puji Astuti, Endah (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Backgroud: Diarrhea was one of the major causes of morbidity and mortality in the world, especially in developing countries. The incidence of diarrhea in Banguntapan I health center Bantul was the highest from 2013 to 2014. Until now, diarrhea is still considered as a disease that causes extraordinary event (KLB) because its incidence is throughout the year in all provinces in Indonesia. It is reported that patients with diarrhea in Indonesia in 2010 were mostly 12-17 months of age and dominant in male. One of the main faktors that cause diarrhea is infection (bacterial infections, viral infections, parasitic infections, orparenteral infections). Objective: To determine the incidence of diarrhea in children under five years in Banguntapan I health center Bantul Yogyakarta. Methods: This studi was a quantitative descriptive research. Population in this research was all children aged 1-5 years suffering from diarrhea at Banguntapan I health center Bantul in the year of 2014 with a consecutive total sampling method. The amount of the sample was 114 children. Univariate analysis of a percentage was conducted. Results: The respondents were mostly 1-3 years old (73,7%), and male (55,3%). The incidence of diarrhea wasmostly non-infectious diarrhea (88,6%). The majority of children lived in Baturetno village (44,7%), with good nutritional status (78,1%) and a history of measles immunization (100%). Conclusion: The incidence of diarrhea in Banguntapan I health center was still high. Keywords: Children under five years, Incident Diarrhea